Study the influence of the reinforced material geometrical shape on the internal stresses in the composite materials - Alaa H. Ali (Al-Khwarizmi College of Engineering – University of Baghdad, 2007)
In this paper the reinforced materials manufactured from steel continues fibers are used in Aluminum matrix to build a composite material. Most of researches concentrated on reinforced materials and its position in the matrix according to its size and distribution, and their effects on the magnitude of different kinds of the stresses, so this paper presents and concentrate on the geometrical shape of reinforced material and its effects on the internal stresses and strains on the composite strength using FEM as a method for analysis after loaded by certain force showing the deference magnitudes of stresses according to the different geometrical shapes of reinforced materials.